2014
DOI: 10.1039/c4ra06548d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melting temperature on interfacial interaction and mechanical properties of polypropylene (PP) fiber reinforced olefin block copolymers (OBCs)

Abstract: Transcrystalline structures for the first time were observed at the interface of OBC/PP fiber, proving that the partially melted (170 °C) and totally melted (190 °C) PP fibers have stronger interactions with OBC than unmelted PP fibers does.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…This relationship is in accord with the general tendency that meltingp oints of organic compounds become higher when intermoleculara ttractivef orces, such as those arising from bonding orbitali nteractions, becomelarger in crystals. [51][52][53][54] Thus, the relationship suggestst hat intermolecular orbital interactions elongate l FL,C of 1a-gBF 2 .N ote that the S 0 -S 1 electronic transitions in the molecular arrays of 1fBF 2 and 1gBF 2 do not contribute to the FL emission because they are forbidden.T hus, other allowed S 0 -S n transitions are involved in FL emission of 1fBF 2 and 1gBF 2 . In fact, meltingp oints and experimentallyd etermined energies for fluorescencee mission of 1a-gBF 2 in crystals( E FL,C ), which were calculated from l FL,C ,a lso show linear relationships, except in the cases of 1fBF 2 and 1gBF 2 (Figure 8b).…”
Section: Packing-structure-dependent Fl Propertieso Fcrystalsmentioning
confidence: 95%
“…This relationship is in accord with the general tendency that meltingp oints of organic compounds become higher when intermoleculara ttractivef orces, such as those arising from bonding orbitali nteractions, becomelarger in crystals. [51][52][53][54] Thus, the relationship suggestst hat intermolecular orbital interactions elongate l FL,C of 1a-gBF 2 .N ote that the S 0 -S 1 electronic transitions in the molecular arrays of 1fBF 2 and 1gBF 2 do not contribute to the FL emission because they are forbidden.T hus, other allowed S 0 -S n transitions are involved in FL emission of 1fBF 2 and 1gBF 2 . In fact, meltingp oints and experimentallyd etermined energies for fluorescencee mission of 1a-gBF 2 in crystals( E FL,C ), which were calculated from l FL,C ,a lso show linear relationships, except in the cases of 1fBF 2 and 1gBF 2 (Figure 8b).…”
Section: Packing-structure-dependent Fl Propertieso Fcrystalsmentioning
confidence: 95%
“…For example, OBCs with different block architectures during uniaxial deformation were investigated and it was found that longer but fewer hard blocks in the OBCs resulted in fewer folded-chain lamellar crystals, a less effective network and an easier break, especially at high temperatures. 16 From the viewpoint of optimization of properties, there have been reports on enhanced mechanical strength via blending, 17 ber reinforcing [18][19][20] and ller reinforcing. 15 Furthermore, the structure and properties of OBCs can also be inuenced by external elds such as processing temperature and shear ow.…”
Section: Introductionmentioning
confidence: 99%
“…The interface between the resin matrix and fiber is one of the important factors that decide the final mechanical properties of polymer/fiber composites. Here, the surface tensions of copolymers PPS‐NH 2 and GF were calculated from the following equation: γltrue(1+cos θtrue)=2γnormalsdγnormalld+2γnormallp; γnormalld+rnormallp; γs=γnormalsd+γnormalsp where γnormall is surface tension of standard solution, γs is surface tension of solid. θ is contact angle, γsd and γsp are the disperse part and polar part of solid, respectively, γld and γlp are the disperse part and polar part of standard solution, respectively.…”
Section: Resultsmentioning
confidence: 99%